Relation of third and fourth heart sounds to blood velocity during left ventricular filling. - Vancheri, F (1989)
To investigate the relation between changes in left ventricular inflow velocity and the timing of third and fourth heart sounds, simultaneous phonocardiograms and continuous wave Doppler traces were recorded in 48 patients (aged 17-78) with heart disease and in 21 normal children. The onset of the first vibration of the third heart sound coincided with peak left ventricular inflow blood velocity to within 5 ms in all but two of the patients. The mean (SD) difference between the two events was 5 (5) ms, which did not differ significantly from zero. The relation was similar in patients with primary myocardial disease (11), and in those with valve disease (26), hypertension (five), and coronary artery disease (four). In the normal children, the mean interval was 2.5 (5) ms--not significantly different from zero. By contrast, the first deflection of the fourth heart sound consistently preceded the timing of peak atrial inflow velocity by 55 (10) ms. Agreement was much closer between the onset of atrial flow and the onset of the atrial sound (mean difference 1 (5) ms, not significantly different from zero). Gallop sounds seem to be closely related to changes in ventricular inflow velocity, and thus to the effects of forces acting on blood flow. The forces underlying the third sound seem to arise within the ventricle and are responsible for sudden deceleration of flow during rapid ventricular filling. The fourth sound, occurring at the onset of the "a" wave, is more likely to arise from dissipation of forces causing acceleration of blood flow--that is, atrial systole itself.